2019
DOI: 10.1093/ajhp/zxz197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of discharge medication bedside delivery service on hospital reutilization

Abstract: Purpose To evaluate the impact of a medication to bedside delivery (meds-to-beds) service on hospital reutilization in an adult population. Methods A retrospective, single-center, observational cohort study was conducted within a regional academic medical center from January 2017 to July 2017. Adult patients discharged from an internal medicine unit with at least one maintenance medication were evaluated. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The strength of our study is that this analysis includes quantitative data for a large, diverse population in an urban environment and thus could be applicable to a wide array of hospitals and populations. Previous studies have been limited to hundreds of patients instead of thousands 33 . In addition, by stratifying based on CCI and performing cost analyses, we identified objective criteria with which other institutions can target assistance in a world with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of our study is that this analysis includes quantitative data for a large, diverse population in an urban environment and thus could be applicable to a wide array of hospitals and populations. Previous studies have been limited to hundreds of patients instead of thousands 33 . In addition, by stratifying based on CCI and performing cost analyses, we identified objective criteria with which other institutions can target assistance in a world with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Discharge services can be further expanded by incorporating a meds-to-bed program where medications are delivered to the patient's bedside, patients are offered medication counseling, and barriers to medication access are addressed before discharge. 8 Previous literature has suggested that a meds-to-bed program may have an impact on 30-day hospital readmission when it is also combined with additional transitions-of-care interventions, such as medication reconciliation and postdischarge follow-up. 8…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous literature has suggested that a meds-to-bed program may have an impact on 30-day hospital readmission when it is also combined with additional transitions-of-care interventions, such as medication reconciliation and postdischarge follow-up. 8…”
Section: Discussionmentioning
confidence: 99%
“…The role of a clinical pharmacist at the time of hospital discharge has been well established in the literature. [74][75][76][77] However, there is no liter- being discharged, rather than picking them up on the way home. 76,77 Further, the clinical pharmacist can address questions related to nutritional deficiencies particularly in recommending and determining appropriate supplements that may be available over-the-counter as treatment options.…”
Section: Hospital Discharge/follow-upmentioning
confidence: 99%
“…[74][75][76][77] However, there is no liter- being discharged, rather than picking them up on the way home. 76,77 Further, the clinical pharmacist can address questions related to nutritional deficiencies particularly in recommending and determining appropriate supplements that may be available over-the-counter as treatment options. A clinical pharmacist ensures that the patient has adequate follow-up scheduled, but also address any questions or possible medication discrepancies in 2 to 3 days after discharge.…”
Section: Hospital Discharge/follow-upmentioning
confidence: 99%